PEJORISM IN ALEX LA GUMA’S AND A THREEFOLD CORD - Ogbeide, Victor O. (European Scientific Journal, ESJ, 2013)
This article examines pejorism in Alex La Guma’s And a Threefold Cord. Employing the factors of characterization, setting and language it demonstrates that La Guma could be pejorative, in deference to his Marxist persuasion and his first hand experience, in his literary objective of letting the world know about the plight of the hapless non-whites in the apartheid enclave of South Africa. The implications of pejorism in the novel notwithstanding, it is the contention of this paper that its use by La Guma is not only a function of his realism as a novelist but also a function of his unflagging commitment to the cause of the oppressed, deprived and dehumanized all over the world be they in the wilds of Ajegunle in Nigeria or in the disease-infested slums of Rio de Janeiro’s favelas.